Radiocesium concentrations in wild mushrooms after the accident at the Fukushima Daiichi Nuclear Power Station: Follow-up study in Kawauchi village - Makiko Orita (Nature Portfolio, 2017)
Abstract Since the accident at the Chernobyl Nuclear Power Plant, it has become well known that radiocesium tends to concentrate in wild mushrooms. During the recovery process after the accident at the Fukushima Daiichi Nuclear Power Station (FDNPS), it is important to perform follow-up measurements of the activity concentrations of radiocesium in mushrooms. We evaluated the activity concentrations of the detected artificial radionuclides (radiocesium) in wild mushrooms collected from Kawauchi village, which is within 30 km of the FDNPS, in 2015, four years after the accident. We found that the radiocesium was determined in 147 of 159 mushroom samples (92.4%). Based on the average mushroom consumption of Japanese citizens (6.28 kg per year), we calculated committed effective doses ranging from <0.001 to 0.6 mSv. Although committed effective doses are relatively limited, even if residents have consumed mushrooms several times, continuous monitoring of the radiocesium in mushrooms in Fukushima is needed for sustained recovery from the nuclear disaster.